Implementasi Peraturan Daerah Kabupaten Pringsewu Nomor 07 Tahun 2015 tentang Penyelenggaraan PerlindunganPerempuan dan Anak Korban Kekerasan dalam Upaya Pencegahan Gangguan Kesehatan Mental pada Anak - Mulia Indria Kusuma; Eti Karini; Ahmad Fauzi Furqon (Jurnal Hukum Lex Generalis, 2026)
This study analyzes the implementation of Article 17 Paragraph (1) of Pringsewu Regency Regional Regulation Number 07 of 2015 concerning the Protection of Women and Child Victims of Violence in efforts to prevent mental health disorders among children. The study employed a qualitative method through interviews with the DP3AP2KB and community members. The findings indicate that the policy implementation has not been optimal due to limited public outreach, the uneven implementation of the Child-Friendly School Program and the low level of public mental health literacy. The main obstacles include limited budget allocation and inadequate human resources. From the perspective of siyasah tanfidziyyah, these conditions are not yet consistent with the principles of hifz al-nafs (protection of life) and hifz al-‘aql (protection of intellect). Therefore, strengthening policy implementation is necessary through expanded public outreach, increased budget support and enhanced inter-agency collaboration.